Health Cadres Empowerment with Complementary Food Workshops and Cooking Class - Firlia Ayu Arini; Nur Intania Sofianita; Apriningsih Apriningsih; Nanang Nasrullah (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT The first 1000 days of life is the critical period for stunting prevention. After exclusive breastfeeding, the adequacy of complementary feeding determines children's growth. In the community, some problems found in complementary feeding practices, include early introduction and suboptimal feeding, which are low in diversity, frequency, and unsuitable texture for the children’s age group. Every subdistrict has a Posyandu (Health Integrated Service Post) organized by health cadres. To help stunting prevention, it is important to empower the health cadres with a complementary food workshop and cooking class to gain the cadres knowledge and skills that are useful for their role in organizing Posyandu and conducting supplementary feeding program. To analyze the improvement of health cadres' knowledge and skills about complementary feeding using local food. The design of this community service program were a workshop about complementary feeding followed by discussion to compose menus of complementary food  and cook them in the cooking class. A total 16 health cadres participated in this program, they were from Pengasinan and Bedahan Ward, Depok City. To measure the effectiveness of the workshop, we collected pre-post questionnaire about complementary feeding. Based on the paired t-test, there is a significant difference between pre and post-test on the health cadres’ knowledge. The mean of the post-test was 15 score higher than the pre-test. It was concluded that the workshop and cooking class of compelementary food has improved health cadres knowledge. Hopefully, the cadres might educate mothers with children under two about complementary feeding practice at Posyandu to help reduce and prevent stunting. Keywords: Complementary Food, Health Cadre, Workshop, Cooking Class.